Narancssárga tulipánok – A néderlandisztika szak története a Debreceni Egyetemen - Pusztai, Gábor (Gerundium, 2016)
Orange-Yellow Tulips. The History of Dutch Studies at the University of Debrecen. Teaching of Dutch started at Lajos Kossuth University (which later became the University of Debrecen) with a group of five students in 1991. At that time, Dutch was offered as a second Germanic language to students of German only. Currently, there are four different types of study programmes at the independent Department of Dutch Studies, with more than 90 students altogether. The popularity of Dutch Studies is partially a result of the excellent opportunities in the labour market for candidates speaking Dutch.